Analysis of the debate on the concept of the state and citizens in the BPUPK meeting treatise - Syarifa, Syifa; Japar, Muhammad; Maiwan, Mohammad; Hamzah, Intan Suria Binti; Fadillah, Dini Nur (Universitas Negeri Yogyakarta, 2022)
In the learning of Pancasila and Civic Education, discussions about BPUPK are often attached to the debates about the formulation of Pancasila as the national principle. In fact, the debates in the BPUPK meeting did not only concern to the national principle, but also about the concept of the state and the citizen. This research aims to analyze how the debate over the concept of the state and citizen is in the treatise of the BPUPK meeting. This research used a qualitative approach with library research methods and qualitative data analysis techniques. The results of this research showed that the debate on the concept of the state was divided into two, namely the debate in the form of the state which is faced with the form of a unitary state, union state and state union, and the debate in the form of government which was faced with the monarchy and republic. Furthermore, the debate about citizens was also divided into two, namely the debate on citizenship for foreign descendants which debates whether or not to make foreign descendants as Indonesian citizens in the Constitution, and the debate on the rights of citizens that debates whether to include or not, the rights of citizens in the Constitution.